CFD model of coupled thermal processes within coke oven battery as an example of complex industrial application - Nowak, A. J.; Smołka, J.; Fic, A.; Kosyrczyk, L. (Computer Assisted Methods in Engineering and Science, 2010)
This paper describes results of the mathematical modelling of steady-state and transient physical phenomena taking place in the heating channels of a coke oven battery. A formulated system of standard Computational Fluid Dynamics (CFD) equations coupled with User Defined Functions is solved numerically using commercial software Ansys Fluent. Finally, the developed 3-D model is used to examine the influence of selected operating parameters on the resulting temperature, velocity and concentration fields within considered object. The obtained results are briefly discussed considering their physical correctness related to industrial measurements.